Crystal structure of the superantigen staphylococcal enterotoxin type A. - Schad, E M (1995)
Staphylococcal enterotoxins are prototype superantigens characterized by their ability to bind to major histocompatibility complex (MHC) class II molecules and subsequently activate a large fraction of T-lymphocytes. The crystal structure of staphylococcal enterotoxin type A (SEA), a 27 kDa monomeric protein, was determined to 1.9 A resolution with an R-factor of 19.9% by multiple isomorphous replacement. SEA is a two domain protein composed of a beta-barrel and a beta-grasp motif demonstrating the same general structure as staphylococcal enterotoxins SEB and TSST-1. Unique for SEA, however, is a Zn2+ coordination site involved in MHC class II binding. Four amino acids including Ser1, His187, His225 and Asp227 were found to be involved in direct coordination of the metal ion. SEA is the first Zn2+ binding enterotoxin that has been structurally determined.